Family experiences and attitudes toward care of ICU patients with delirium: A scoping review - Lange, Sandra; Mȩdrzycka-Da̧browska, Wioletta; Friganović, Adriano; Religa, Dorota; Krupa, Sabina (Frontiers in Public Health, 2022)
Introduction The family has an important role in the care of the ICU patient. Research shows that the implementation of non-pharmacological interventions to prevent delirium, including interventions with the family, can reduce the incidence of delirium. The aim of this review was to search the available literature about the experiences and attitudes of family/carers of ICU patients diagnosed with delirium during hospitalization. Methods A scoping review method was used to map terms relevant to the involvement of relatives in the care of critically ill patients with delirium. To identify studies, the following databases were searched: PubMed, Scopus, EBSCO, Web of Science, and Cochrane Library. The database search was ongoing from 15 July 2022, with a final search on 4 August 2022. Results Thirteen articles reporting on the experiences and attitudes of family/carers of ICU patients who developed delirium during hospitalization were included in the scoping review. Of the included studies, eight were qualitative studies, three were quantitative studies and two were reviews (systematic review and integrative review). The studies were conducted in North America, Europe, South Africa, and Asia. Our findings show that carers experienced adverse effects associated with delirium in ICU patients such as stress, anxiety, embarrassment, uncertainty, anger, shock. Families/relatives need both emotional and informational support from medical staff. Conclusion Relatives want to be involved in the care of the delirium patient, although this needs improvement in some aspects of care such as: lack of awareness, family/relatives knowledge of delirium, improved education, and communication with medical staff. Recognition of delirium by families is acceptable and feasible. Family involvement may induce an increased anxiety, but this aspect needs further research.